AUDIT OPERASIONAL ATAS PERSEDIAAN BARANG DAGANG PADA PT. INDOMURAYAMA PRESS & DIES INDUSTRIES - Budi Tri Rahardjo, Ak., M.Ak., CA; Ainul Baroroh (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2015)
Reason and Research Purposes. Want to know the application is made PT. Indomurayama Press & Dies Industries in Operational Audit on Merchandise Inventoy Want to know the level of effective and economical merchandise inventoy for the company. Research Purposes Descriptive qualitative methods of analysis based on the depiction that support the analysis. Results Purposes and Findings The Company has not implemented Operational Audit so companies are still not operating effectively and economically.